2021
DOI: 10.1055/s-0041-1736581
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Rates of RSV Hospitalization among Preterm Infants: A Decade of Data

Abstract: Objective In 2014, the American Academy of Pediatrics (AAP) changed its policy on the use of respiratory syncytial virus immunoprophylaxis (RSV-IP) so that RSV-IP was no longer recommended for use among infants without other medical conditions born >29 weeks gestational age (wGA). This study examines 10-year trends in RSV-IP and RSV hospitalizations among term infants and preterm infants born at 29 to 34 wGA, including the 5 RSV seasons before and 5 RSV seasons after the AAP guidance change. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“… 23 Higher rates of RSVH and lower rates of palivizumab use have also been reported in preterm infants aged 29–34 wGA at birth following the policy change, 16 , 21 , 24 , 29 and these changes persisted for five years after the change in guidance. 6 Higher rates of ICU admission, mechanical ventilation, and longer hospitalization duration in infants born at 29–34 wGA with RSVH have also been observed following this change in policy. 30 Despite consistent evidence of these unintended consequences in very preterm infants, for whom the AAP has consistently recommended palivizumab prophylaxis, AAP policy was renewed without revision in 2019.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 23 Higher rates of RSVH and lower rates of palivizumab use have also been reported in preterm infants aged 29–34 wGA at birth following the policy change, 16 , 21 , 24 , 29 and these changes persisted for five years after the change in guidance. 6 Higher rates of ICU admission, mechanical ventilation, and longer hospitalization duration in infants born at 29–34 wGA with RSVH have also been observed following this change in policy. 30 Despite consistent evidence of these unintended consequences in very preterm infants, for whom the AAP has consistently recommended palivizumab prophylaxis, AAP policy was renewed without revision in 2019.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research has described trends in palivizumab use and RSVH among term and preterm infants, 6–27 but limited data are available for very preterm infants. 10–12 The primary objective of the current study is to characterize palivizumab prophylaxis and risk of RSVH among very preterm (<29 wGA) infants and to compare the RSVH course among very preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…28 Kong et al found significant increases in relative rates of RSVH following the policy change among infants born at 29 to 34 wGA for both commercially insured infants (1.95; 95% confidence interval [CI]: 1.67–2.27, p < 0.001) and Medicaid-insured infants (1.70; 95% CI: 1.55–1.86, p < 0.001). 35 In the retrospective database study by Fergie et al, 37 RSVH among infants born at 29 to 34 wGA nearly doubled, from 8.7% before to 14.2% after the policy change ( p < 0.0001). Using a similar strategy with a different claims database, Krilov et al also reported an increase in RSVH (relative risk: 1.55, 95% CI: 1.10–2.17, p = 0.011).…”
Section: Discussionmentioning
confidence: 97%
“…This difference is comparable to the effect seen in infants with the same characteristics enrolled in controlled trials, where the weighted mean rate ratio was 4.9. 19,46,47 Several studies have used data from administrative databases to assess the effectiveness of palivizumab for preventing RSVH in moderate/late premature infants in the realworld setting, revealing a significant increase in RSVH among otherwise healthy infants born after 29 to 34 wGA, [32][33][34][35] that correlates with the loss of eligibility for prophylaxis in this population after implementation of the 2014 AAP guidelines. 28 Kong et al found significant increases in relative rates of RSVH following the policy change among infants born at 29 to 34 wGA for both commercially insured infants (1.95; 95% confidence interval [CI]: 1.67-2.27, p < 0.001) and Medicaid-insured infants (1.70; 95% CI: 1.55-1.86, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation